Nuevos retos y grandes oportunidades tecnológicas para los sistemas arroceros: producción, seguridad alimentaria y disminución de la pobreza en América Latina y el Caribe - Sanint, Luis Roberto (International Center for Tropical Agriculture, 2010)
New challenges and great technological opportunities for rice systems: Production, food security, and mitigation of poverty in Latin America and the Caribbean The status of rice production worldwide and particularly in Latin America and the Caribbean (LAC) is examined, highlighting the important role it plays in food security and in the reduction of poverty in the region. Thanks to the rapid adoption of improved varieties, rice production tripled in LAC between 1985 and 2005, reaching 25 million tons paddy rice. At the same time, the area planted to the crop remained stagnant at 6 million hectares, as upland rice has been quickly replaced by irrigated rice. In 1976, over 6.0 million hectares were planted to upland rice, accounting for over 75% of the region’s rice-growing area. With the introduction of new semi-dwarf varieties in the 1970s, upland rice lost its ability to compete with irrigated rice because of the latter’s rapid increase in yields and the decrease in unitary production costs. The area planted to upland rice has now plunged to less than 2.5 million hectares (40% of the area planted to rice in LAC), located mainly in the Brazilian cerrados. The average yield of upland rice, 3.8 t/ha is still low. To close the gap, improved crop management practices are needed so that varieties can fully express their yield potential. Estimates are that rice production in the 12 LAC countries could increase by 27%, in other words by 2.7 million MT. In the 20th century, consumption increased from less than 10 to close to 30 kg/capita per year. The region’s level of self-sufficiency has remained at around 90%. The reduced capacity of governmental institutions for agricultural research and rural extension has forced public institutions to become crucial partners of rice farmers. In 1995, several LAC countries created the Latin American Fund for Irrigated Rice (FLAR), which is mainly funded by the rice sectors of member countries, with the participation of national and international research institutions as well as partners of the private sector. The challenges and opportunities of the LAC rice sector, especially its participation in the nutrition and food security of the low-income population, are analyzed and the potential of this region to become the rice basket of the world is highlighted in view of its abundant water, land, human, and technological resources.